Electrophoretic Deposition of Chitosan/45S5 Bioactive Glass Composite Coatings Doped with Zn and Sr - Miola, Marta; Verné, Enrica; Ciraldo, Francesca Elisa; Cordero-Arias, Luis; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2015)
In this research work the original 45S5 bioactive glass (BG) was modified by introducing zinc and/or strontium oxide (6% mol) in place of calcium oxide. Sr was added for its ability to stimulate bone formation, Zn for its role in bone metabolism, antibacterial properties and anti-inflammatory effect. The glasses were produced by means of melting and quenching process. SEM and XRD analyses evidenced that Zr and Sr introduction did not modify the glass structure and morphology, while compositional analysis (EDS) demonstrated the effective addition of these elements inside the glass network. Bioactivity test in simulated body fluid (SBF) up to one month evidenced a reduced bioactivity kinetics for Zn-doped glasses. Doped glasses were combined with chitosan to produce organic/inorganic composite coatings on stainless steel AISI 316L by electrophoretic deposition (EPD). Two EPD processes were considered for coating development, namely direct current EPD (DC-EPD) and alternating current EPD (AC-EPD). The stability of the suspension was analysed and the deposition parameters were optimized. Tape and bending tests demonstrated a good coating-substrate adhesion for coatings containing 45S5-Sr and 45S5-ZnSr glasses, while the adhesion to the substrate decreased by using 45S5-Zn glass. FTIR analyses demonstrated the composite nature of coatings and SEM observations indicated that glass particles were well integrated in the polymeric matrix, the coatings were fairly homogeneous and free of cracks; moreover the AC-EPD technique provided better results than DC-EPD in terms of coating quality. SEM, XRD analyses and Raman spectroscopy, performed after bioactivity test in SBF solution, confirmed the bioactive behaviour of 45S5-Sr containing coating, while coatings containing Zn exhibited no hydroxyapatite formation.